Application of the guided inquiry learning model to increase student learning motivation - Chilya Choirun Nisa; Dyah Astriani (Jurnal Pijar Mipa, 2022)
The purpose of the study was to describe the application of the guided inquiry learning model to increase students' motivation to learn about energy in life topics. This research is a descriptive study involving 20 class VII-E SMP Muhammadiyah Sidoarjo Indonesia students in the Academic Year 2021/2022. This research is pre-experimental research with one group pretest-posttest design. The instruments used are motivational tests and questionnaires. The data analysis technique used is the normality test and the Wilcoxon test. The research data collection was carried out using the test and questionnaire method. The instrument used was a learning motivation questionnaire. Hypothesis testing using the Wilcoxon test. The data analysis and discussion results show an increase in learning outcomes with an average N-Gain of 0.61, which has moderate criteria. Questionnaire responses obtained 87.2% in the high category. The Wilcoxon test showed a significance score of <0.05, meaning a significant difference between the pretest and posttest scores. It can be concluded that applying the guided inquiry model increases learning motivation.